ANALISIS KEMANDIRIAN DAN EFEKTIVITAS KEUANGAN DAERAH KABUPATEN DAN KOTA DI PROVINSI SUMATERA SELATAN SEBELUM DAN SESUDAH PANDEMI COVID-19 - Alfansa, Rayhan; Wibowo, Puji (Universitas Prof.Hazairin,SH Bengkulu, 2022)
The presence of Covid-19 in the early 2000 shocked Indonesia in many aspects. The performance of regional governments in terms of of local budget management was questionable during the pandemic period. The purpose of this study is to analyze impact of Covid-19 pandemic to financial performance in regencies and cities under South Sumatera jurisdiction. This research is analysing the differences of financial independence ratio and financial effectiveness ratio of districts and cities in South Sumatera between before and post-COVID-19 pandemic period. The type of this research is quantitative research in form of comparative research by using saturated sampling. The data collection method which used by author are library method and non-behavioral observation method. The data process method which used by author are analysis method with using t-test and sample collection method. The final results of this research are there are no significant differences for financial independence ratio and there are significant differences for financial effectiveness ratio of districts and cities in South Sumatera between before and after COVID-19 pandemic